PENDIDIK PROTOTIPE DALAM AL-QUR’AN DAN HADITS: PARANABI DAN RASUL SEBAGAI FIGUR ACUAN PENDIDIK - Sayid Ahmad Ramadhan; Taufik Warman Mahfuz (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2025)
This article aims to analyze the criteria for educators as outlined in the Qur'an and Hadith, using the Prophets and Messengers as reference points. A literature review is employed as the research method, oriented toward content analysis to gather and organize the necessary data. The results of the study show that the qualities and behaviors of the Prophets and Messengers, as exemplary figures for educators, are found in the Qur'an and Hadith. These include: first, making faith and moral character the primary keys in education, which bring peace in life both in this world and the hereafter; second, showing equal compassion toward students by consistently offering advice that leads to changes in behavior and mindset; third, always upholding justice during the learning process (knowledge transfer), including when students make mistakes or successfully master and achieve learning objectives, by providing educational rewards and sanctions; fourth, being able to serve as a central figure for students in the process of acquiring knowledge; fifth, being able to maintain emotional and physical stability, especially in managing anger; and sixth, prioritizing consultation and consensus in decision-making rather than imposing one's will on the students